Proceedings of the 2021 CHI Conference on Human Factors in Computing Systems 2021
DOI: 10.1145/3411764.3445362
|View full text |Cite
|
Sign up to set email alerts
|

“It’s About Missing Much More Than the People”: How Students use Digital Technologies to Alleviate Homesickness

Abstract: Homesickness, which refers to feelings of distress caused by separation from home, is prevalent among university-aged students. Chronic homesickness can exacerbate mood problems, erode academic performance and lead to dropout from school. The present research examines how students use digital technologies to resolve the experience of missing home. Qualitative interviews and diaries with 50 students at major Australian universities revealed that technologies play a significant role in alleviating homesickness. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 73 publications
(99 reference statements)
0
4
0
Order By: Relevance
“…The family influence factor was also not supported by the majority of participants in the present study. While some did mention family in the decision to attend college in the US, the use of technology bridged the gap in feeling homesick ( Kelly et al, 2021 ), which lessened the identification of family in the transition process. This study’s results suggest the updated revision for this model should exclude family influence in the adjustment model.…”
Section: Resultsmentioning
confidence: 99%
“…The family influence factor was also not supported by the majority of participants in the present study. While some did mention family in the decision to attend college in the US, the use of technology bridged the gap in feeling homesick ( Kelly et al, 2021 ), which lessened the identification of family in the transition process. This study’s results suggest the updated revision for this model should exclude family influence in the adjustment model.…”
Section: Resultsmentioning
confidence: 99%
“…It could be that those struggling with depression, anxiety, eating disorders, or financial insecurity were unwilling to participate in the study. It is important to point out here that recent studies have shown that mental health varies greatly from person to person during the pandemic ( Kelly et al, 2021 ; Mooney and Becker, 2021 , 2021h lund, 2021 ) and that eating disorders have generally increased ( Zhang, 2021 ). Although we do not assume that for most of them, as most of them declined us politely with sound reasons (such as a lack of time, since the interviews had to be carried out within a narrow time span).…”
Section: Limitations and Future Workmentioning
confidence: 94%
“…While pandemic-induced changes related to education and work (cf. ( Afonso et al, 2020 ; Gaggi et al, 2020 ; Kelly et al, 2021 )) and leisure behavior (cf. ( Benford et al, 2021 ; Niu et al, 2021 ; Yeung, 2020 )) have been explored in recent studies from a human-computer interaction (HCI) perspective, food practices, and in particular the media and technology used during those practices in pandemic times, are rarely examined (cf.…”
Section: Introductionmentioning
confidence: 99%
“…We used a semistructured interview guide, with an initial set of open-ended questions that enabled participants to share their personal experiences (see Multimedia Appendix 1 for the questions). The interview questions were developed as a team, drawing on our collective experience of research on digital communication technologies [ 51 , 52 ], older adults [ 53 , 54 ], and aged care [ 29 , 55 ]. The researcher took notes during the interviews and asked follow-up questions to probe responses in detail.…”
Section: Methodsmentioning
confidence: 99%